2019
DOI: 10.21203/rs.2.9507/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

rpoB, a promising marker for analyzing the diversity of bacterial communities by amplicon sequencing

Abstract: Background Microbiome composition is frequently studied by the amplification and high-throughput sequencing of specific molecular markers (metabarcoding). Various hypervariable regions of the 16S rRNA gene are classically used to estimate bacterial diversity, but other universal bacterial markers with a finer taxonomic resolution could be employed. We compared specificity and sensitivity between a portion of the rpoB gene and the V3V4 hypervariable region of the 16S rRNA gene. Results We first designed univer… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…Rarefaction curves generated on quality-filtered reads indicated that sequencing depth was sufficient (Additional file 2). As previously observed [41], the rpoB marker gave a better taxonomic assignment, with 56% and 32% of the OTUs associated with a genus or species name, respectively (Additional file 5). Based on these results, we pursued the two-marker approach.…”
Section: Optimization Of a Metabarcoding Pipeline For Molecular Descrsupporting
confidence: 76%
See 3 more Smart Citations
“…Rarefaction curves generated on quality-filtered reads indicated that sequencing depth was sufficient (Additional file 2). As previously observed [41], the rpoB marker gave a better taxonomic assignment, with 56% and 32% of the OTUs associated with a genus or species name, respectively (Additional file 5). Based on these results, we pursued the two-marker approach.…”
Section: Optimization Of a Metabarcoding Pipeline For Molecular Descrsupporting
confidence: 76%
“…*OTU present in the control samples Steinernema infective stages. We first molecularly characterised the microbiota of four Steinernema species with two markers, the V3V4 region of the 16S rRNA gene and a 435 bp region of the rpoB gene, because multigene approaches have been shown to improve the reliability of bacterial community description in ecosystems of low complexity [41]. We also characterised the Steinernema microbiota by culture-based methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic DNA was extracted using DNeasy PowerBiofilm Kit (Qiagen), as described by the manufacturer. The number of total bacteria was estimated by quantifying the number of copies of the rpoB gene, which is a single-copy gene 102 . PCR reaction was conducted as described elsewhere 83,103 .…”
Section: Corrosion Experiments Screening Corrosion Test Of Isolatesmentioning
confidence: 99%